Nebulization of High-Dose Poractant Alfa in Newborn Piglets on Nasal Continuous Positive Airway Pressure Yields Therapeutic Lung Doses of Phospholipids - Nord, Anders; Bianco, Federico; Salomone, Fabrizio; Ricci, Francesca; Schlun, Martin; Linner, Rikard; Cunha-Goncalves, Doris (American Journal of Perinatology, 2020)
Objective It is not known how much surfactant must be nebulized to reach a lung dose of phospholipids equivalent to that obtained by the instillation of 200 mg/kg of surfactant. We aimed to assess the feasibility of nebulizing a high-dose of poractant alfa with the eFlow-Neos investigational vibrating-membrane nebulizer in newborn piglets on nasal continuous positive airway pressure (nCPAP) and to determine whether this intervention would yield therapeutic lung doses of phospholipids.Study Design Twelve 1-day-old piglets on nCPAP received 600 mg/kg of poractant alfa admixed with technetium-99m via nebulization. Six piglets receiving 200 mg/kg of instilled synthetic surfactant served as controls. Lung deposition (percentage of the nominal dose) was determined by gamma scintigraphy, and the phospholipids' lung dose was calculated.Results The lung dose of phospholipids (mean ± standard deviation [SD]) was 138 ± 96 mg/kg with nebulization, and 172 ± 24 mg/kg with instillation (p = 0.42). Nebulization took 58 ± 12 minutes. The arterial partial pressure of carbon dioxide increased from 6.7 ± 1.1 to 7.2 ± 1.1 kPa during nebulization (p = 0.04). Cerebral oximetry remained stable, and there was no hemodynamic instability.Conclusion Nebulization was well tolerated, and the mean lung dose of phospholipids was above 100 mg/kg, that is, not different from the instillation group. These experimental findings suggest that it may be feasible to reach therapeutic lung doses of phospholipids by surfactant nebulization during nCPAP.Key Points
Keywords: deposition; aerosolization; noninvasive ventilation; neonatal respiratory distress syndrome; surfactant